Evolution of the north east rift zone of Tenerife, Canary Islands : a multi-disiplinary approach - Delcamp, Audray (Trinity College (Dublin, Ireland). Department of Geology, 2010)
Tenerife Island, Canary archipelago, is at the centre of intense geological research and debate. The island is composed by three principal rift-zones that enclose major collapse structures. This study provides a multi-disciplinary approach to constrain better the development of the North-East Rift-Zone (NERZ) and its link with destabilisation periods manifested in lateral collapse events. Dyke orientation patterns in the field imply that flanks of the NERZ were slowly creeping over extended periods of time to accommodate the emplacement of an intrusive complex(es) and its associated dykes. Paleomagnetic data from NERZ mafic dykes and the associated host rocks of the upper part of the NERZ suggest they were rotated 26° clockwise about a vertical axis. This rotation is interpreted as the consequence of flank creeping that induced strike-slip movements into the edifice. The existence of intrusive complex(es) below the rift and its role in the deformation of the NERZ have been highlighted by AMS analyses and scaled analogue models. The development of the rift and the intrusive complex(es) are inherently linked and bring the system ultimately towards an unstable configuration and at that point, creeping cannot accommodate deformation any longer, and further intrusions will generate a collapse. The architecture and development of the NERZ thus contrasts with the widely held beliefs that rift-zones arc simple linear arrangement of fractures, dyke swarms, and volcanoes. The North-East rift-zone is a dynamic and changing environment, with several intense intrusive phases concordant or alternating with erosion periods and destabilisation events.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin